PENERAPAN KONSEP ANALISA STANDAR BELANJA PADA PENYUSUNAN ANGGARAN KEGIATAN BIMBINGAN TEKNIS DI KABUPATEN KUNINGAN - , Sari Narulita ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to apply the analysis concept of expenditure standart on expenditure budget of technical guidance activity as one of the handbook in evaluating an activityâs cost equity. The data in this research is secondary data based on the 2008 local expenditure and revenue budget (APBD 2008). Simple regression analysis method is used as the analytical method, whereas the expenditure standart analysis expansion method refer to framing expenditure standart analysis (ASB) elaborating by Program Magister Akuntansi Fakultas dan Bisnis UGM. Research methodology is done with two approaches, libarary research and field research. The result of the research shows that there is unsignficant overfinancing budget necessity based on expenditure standart analysis from twelve technical guidance activities in Kuningan district upon 2008 period. However, there is primness cost allocation for some activities toward expenditure details in each segment of the local government. They are non-civil servant honorarium expenditure, material expenditure, food and beverages expenditure, and official trip expenditure. Unappropriate budget allocation with standart rate, uneffective assignment volume determination, and inefficient budget allocation are found in all expenditure details.